Hak Atas Pekerjaan Bagi Perempuan Pada Perusahaan Ojek Online Berdasarkan Prinsip Kesetaraan Substantif dan Prinsip Non Diskriminasi - Virgayani Fattah (Faculty of Law, Universitas Airlangga, 2022)
AbstractEquality is a pillar for every democratic society that has the goal of achieving social justice and human rights. The fact is that in every community and activity environment, women are subjected to different treatment in law and reality. This situation is both caused and exacerbated by discrimination in the family, community, and workplace.In general, granting rights to women is the same as granting rights to men, this also applied to the right to employment. Women may work in various fields, inside or outside their homes, either independently or with other people, with government or private institutions, as long as the work is carried out in an atmosphere of respect and courtesy. Women can maintain their religion and avoid the negative impacts of the job on themselves and their environment. The Reformation Order was the most progressive period in the protection of human rights in Indonesia. Various laws and regulations were issued during this period, including legislation on the right to employment for women. This is an effort by the government to eliminate discrimination based on sex which is included in various laws and regulations. The law is required to be fair and gender-responsive to ensure the fulfillment of women’s rights, as well as the right to work for women in the online taxi sector. Based on the principle of equality and the principle of non-discrimination, men and women have equal rights or opportunities to participate in every aspect of social and state life, so that if there is discrimination against women, it is a form of violation of women’s rights.Keywords: Equality; Non-Discrimination; Women’s Right. AbstrakKesetaraan merupakan pilar bagi setiap masyarakat demokratis yang mempunyai cita-cita mencapai keadilan sosial dan hak asasi manusia. Kenyataannya dalam setiap lingkungan masyarakat dan lingkungan kegiatan, perempuan menjadi sasaran dari perlakuan yang berbeda dalam hukum maupun dalam kenyataan yang sesungguhnya. Keadaan ini disebabkan dan juga diperburuk oleh adanya diskriminasi di dalam keluarga, masyarakat dan tempat kerja. Pada umumnya pemberian hak bagi perempuan sama dengan pemberian hak kepada laki-laki, demikian halnya dengan hak atas pekerjaan. Perempuan boleh bekerja dalam berbagai bidang, di dalam ataupun di luar rumahnya, baik secara mandiri maupun bersama orang lain, dengan lembaga pemerintah ataupun swasta, selama pekerjaan tersebut dilakukannya dalam suasana terhormat dan sopan, selama mereka dapat memelihara agamanya, serta dapat menghindari dampak-dampak negatif dari pekerjaan tersebut terhadap diri dan lingkungannya. Orde Reformasi merupakan periode paling progresif dalam perlindungan hak asasi manusia. Berbagai peraturan perundangan-undangan keluar pada periode tersebut, termasuk peraturan perundangan-undangan tentang hak bekerja bagi perempuan. Hal ini merupakan upaya pemerintah untuk menghilangkan diskriminasi berdasarkan jenis kelamin yang dicantumkan dalam berbagai peraturan perundang-undangan. Hukum dituntut untuk berkeadilan dan responsif gender untuk menjamin terpenuhinya hak asasi perempuan, demikian halnya terhadap hak atas pekerjaan bagi perempuan di sektor ojek online. Berdasarkan Prinsip Kesetaraan dan Prinsip Non-Diskriminasi antara laki-laki dan perempuan mempunyai hak atau kesempatan yang sama untuk berpartisipasi dalam setiap aspek kehidupan bermasyarakat dan bernegara, sehingga apabila terjadi diskriminasi terhadap perempuan, hal itu merupakan bentuk pelanggaran terhadap hak asasi perempuan.Kata Kunci: Kesetaraan; Non-Diskriminasi; Hak Perempuan.